Qualifizierung von Studierenden des Grund- und Förderschullehramts für Inklusion in Schule und Unterricht - Franzen, Katja; Albers, Timm; Hellmich, Frank (Qualifizierung für Inklusion. Grundschule)
Inklusion ist als Thema aus dem deutschen Bildungssystem nicht mehr wegzudenken und trotzdem stellt sie weiterhin eine Herausforderung auf unterschiedlichen Ebenen dar. Die Qualifizierung der pädagogischen Fachkräfte ist dabei neben der Bereitstellung adäquater Rahmenbedingungen als ein besonders wichtiges Handlungsfeld zu betrachten. Die Bände der Reihe „Qualifizierung für Inklusion“ greifen den bestehenden Forschungs- und Entwicklungsbedarf auf und geben einen Überblick über die Ergebnisse der vom BMBF im Rahmen des Programms „Qualifzierung der pädagogischen Fachkräfte für inklusive Bildung“ geförderten Forschungsprojekte. Adressiert werden damit sowohl Wissenschaftler:innen als auch mit dem Themenfeld Inklusion befasste Personen und Institutionen der Aus-, Fort- und Weiterbildung, der Bildungsadministration und der Bildungspolitik. Der zweite Band der Reihe versammelt die Vorstellung von Projekten, Ergebnissen und Materialien, die sich dem Bildungsbereich der Grundschule zuordnen lassen. Die Reihe besteht aus drei weiteren Bänden, in denen die Ergebnisse zur Qualifizierung für Inklusion im Elementarbereich (Band 1), in der Sekundarstufe (Band 3) sowie in der Berufsschule, Hochschule und Erwachsenenbildung (Band 4) vorgestellt werden.

Primary School Principals’ Views on the Required Conditions for a Successful Implementation of Inclusive Education - Görel, Gamze; Hellmich, Frank (Australasian Journal of Special and Inclusive Education)
Abstract Following the United Nations Convention on the Rights of Persons With Disabilities, questions concerning the joint education of students with and without special educational needs remain to be answered. Currently, there is a need for knowledge about the necessary conditions for a successful implementation of inclusive education. Thus, the aim of the present study is to identify conditions for the implementation of inclusion that are seen as necessary by primary school principals. Therefore, 32 primary school principals were interviewed. The results of the interview study reveal that factors like personnel, financial and material resources as well as building infrastructure in primary schools are seen as important requirements for the successful realisation of inclusive education. Apart from that, the importance of attitudes towards inclusion and sociopolitical conditions for the realisation of inclusion became apparent. Further conditions, which are mentioned from the interviewed principals’ point of view, are related to teacher training, appropriate class sizes and, for example, opportunities for exchanging information. The results of the study indicate that there are essential obstacles as perceived by primary school principals that can impede the implementation of inclusion in primary schools.
Keywords: General Engineering

Qualität der Erfahrungen aus dem inklusiven Unterricht und Selbstwirksamkeitsüberzeugungen von Grundschullehrkräften - Franzen, Katja; Moschner, Barbara; Hellmich, Frank (Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung)

Adaptiver Unterricht in der (inklusiven) Grundschule aus der Perspektive von Lehrkräften - Löper, Marwin Felix; Hellmich, Frank (Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung)

FRIEND-SHIP Intervention Program – The Handbook - Aroni, Katerina; Toulia, Anastasia; Alves, Sílvia Regina Gonçalves; Hassani, Sepideh; Heidrich, Franziska Anna; Franzen, Katja; Görel, Gamze; Löper, Marwin Felix; Aguiar, Teresa; Silveira-Maia, Mónica; Sanches-Ferreira, Maria Manuela Pires Sanches; Hellmich, Frank; et al.

Schlussbericht: Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen (BiFoKi) Entwicklung und Evaluation eines interdisziplinären Fortbildungsangebots - Lütje-Klose, Birgit; Wild, Elke; Gorges, Julia; Neumann, Phillip; Grüter, Sandra; Weber, Antonia

Der Rollenhut als Vermittlungsmedium - Rollenklärungsprozesse im Kontext multiprofessioneller Kooperationen als Thema universitärer Aus- und Fortbildungen von Lehrkräften und Sozialpädagog*innen - Neumann, Phillip; Hopmann, Benedikt; Lütje-Klose, Birgit (Herausforderung Lehrer*innenbildung - Zeitschrift zur Konzeption, Gestaltung und Diskussion)
Multiprofessionelle Kooperation zwischen allgemeinen und sonderpädagogischen Lehrkräften und mit weiteren Fachkräften, u.a. der Schulsozialarbeit, der Schulpsychologie und mit Schulbegleitungen, gilt bei der Entwicklung inklusiver Schulen als zentrale Stellschraube. Dementsprechend wird Kooperation im Kontext Schule auch in der universitären Ausbildung von zukünftig miteinander kooperierenden Professionen sowie in Fortbildungen für Lehrkräfte und multiprofessionelle Teams verstärkt ins Blickfeld gerückt. Zugleich lässt sich beobachten, dass in inklusiven Schulen bislang vermeintlich klare Zuständigkeiten, insbesondere zwischen Sonder- und Sozialpädagog*innen, aufweichen und neu austariert werden müssen. Bei der Entwicklung multiprofessioneller Teams gilt die Klärung von Rollen und Aufgaben als eine besondere Herausforderung, wenn unterschiedliche Professionen mit unterschiedlichen institutionellen Anbindungen und pädagogischen Zielperspektiven oder Grundhaltungen mitei-nander kooperieren. Das vorgestellte Instrument – der Rollenhut – dient dazu, in multiprofessionellen Gruppen eine individuelle Reflexion über die eigenen Aufgaben anzustoßen und auf dieser Grundlage gemeinsam über die gegenseitigen Erwartungen und Rollen zu diskutieren. Das Instrument wurde im Kontext von Fortbildungen multiprofessioneller Teams an Schulen konzipiert und auch im Rahmen der universitären Lehrer*innenbildung erprobt.

Teachers Between a Rock and a Hard Place: Goal Conflicts Affect Teaching Motivation Mediated by Basic Need Satisfaction - Gorges, Julia; Neumann, Phillip; Störtländer, Jan Christoph (Frontiers in Psychology)
Teaching is a highly demanding profession that requires handling multiple and potentially contradictory goals. Therefore, it is likely that teachers experience conflict between work-related goals on a daily basis. Intraindividual goal conflict may occur when individuals pursue multiple goals drawing on the same limited resources (resource-based goal conflict), or when two or more goals are incompatible in terms of goal attainment strategy or desired end states (inherent goal conflict). Because goal conflict is typically associated with negative effects such as attenuated motivation and wellbeing, teacher goal conflict may jeopardize teaching motivation. This cross-sectional study investigated the effects of in-service teachers’ ( N = 302) goal conflicts on their autonomous (intrinsic and identified regulation) and controlled (introjected and extrinsic regulation) teaching motivation and tested the satisfaction of teachers’ basic need for autonomy, competence, and relatedness as mediators. In line with our hypotheses, results from structural equation modeling showed that frequently experiencing resource-based goal conflict leads to a lower satisfaction of the basic need for autonomy, which, however, was unrelated to teaching motivation. In contrast, frequently experiencing inherent goal conflict attenuates the satisfaction of the basic need for competence, which, in turn, positively predicted autonomous teaching motivation and negatively predicted extrinsic regulation. As expected, relatedness was not associated with the experience of goal conflict. The discussion focuses on differential effects of the two types of goal conflict on teaching motivation and on the relevance to expand research on teachers’ intraindividual goal conflicts.
Keywords: General Psychology

Validation of the student version of the Perceptions of Inclusion Questionnaire in primary and secondary education settings - Knickenberg, Margarita; Zurbriggen, Carmen L. A.; Schwab, Susanne (SAGE Open)
Considering students’ voices and perspectives is indispensable in educational contexts. Therefore, instruments of measurement that are reliable and valid and can be used easily without complications are needed in schools. The Perceptions of Inclusion Questionnaire (PIQ) is a short instrument used to assess three central dimensions of inclusion, namely emotional and social inclusion and academic self-concept. Previous evaluations indicate in general high psychometric properties. This study aimed to evaluate the construct validity of the three scales of the PIQ’s student version using different approaches in two samples from primary (grade 4, N = 721) and secondary (grade 7, N = 393) schools. The results of confirmatory factorial analyses confirmed the PIQ’s three factors in both samples which are also measurement equivalent across grades. Plausible correlations with additional divergent and convergent scales reveal that the PIQ measures the theoretically assumed constructs—emotional and social inclusion as well as academic self-concept—validly.
Keywords: General Social Sciences; General Arts and Humanities

Brave New Kachel-World? Über Zoom-Booming, Datenkontrolle und öffentliche Infrastrukturen - Weber, Jutta (Von Menschen und Maschinen – Mensch-Maschine-Interaktionen in digitalen Kulturen)